Four meroterpenoids from Alternaria alternata isolated from Paeonia lactiflora. (June 2019) - Wang, Ju-Tao; Ma, Zong-Hui; Wang, Guo-Kai; Xu, Feng-Qing; Chen, Lin; Yu, Yang; Wang, Gang; Liu, Jin-Song
Graphical abstract: Highlights: Four new natural meroterpenoids, tricycloalternarenes (TCAs) compounds were isolated from Alternaria alternate . Four new TCAs were elucidated by in-depth analyses of NMR spectra, HRESIMS and optical rotation experiments. Cytotoxic activities against five selected tested tumor cell lines of four new TCAs were evaluated. Abstract: Four new natural meroterpenoids, tricycloalternarenes (TCAs)15b‒18b (1 ‒4 ) along with four known TCAs (5 ‒8 ) have been isolated from the fermentation broth of Alternaria alternata derived from Paeonia lactiflora . The structures of compounds1 ‒4 were elucidated by in-depth analyses of NMR spectra, HRESIMS and optical rotation experiments. Cytotoxic activities of1 ‒4 against five selected tumor cell lines were evaluated.